2014
DOI: 10.1177/0309132514527039
|View full text |Cite
|
Sign up to set email alerts
|

Cartography III

Abstract: In this third report, I focus on cognitive cartography in order to examine how the historical division between empiricist and critical approaches in cartography has shifted recently. I do so by building on Kitchin and Dodge’s argument (2007) that parts of the apparent disjuncture within cartography might be resolved through a greater focus on emergent approaches to mapping as a process, which is the core idea of post-representational cartography. By looking at cognitive cartography from a post-representational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 66 publications
0
15
0
1
Order By: Relevance
“…According to Asdal (2015), documents and illustrations contribute to modifying and transforming reality, referred to as modifying work. In the map creation process, subjective decisions are made about what to include, how the map should look, what it should communicate, and so on (Caquard, 2015). In other words, maps not only represent and reveal the world, they also help create that view of the world into being.…”
Section: Theoretical Concepts: Bridging Cartography and Stsmentioning
confidence: 99%
“…According to Asdal (2015), documents and illustrations contribute to modifying and transforming reality, referred to as modifying work. In the map creation process, subjective decisions are made about what to include, how the map should look, what it should communicate, and so on (Caquard, 2015). In other words, maps not only represent and reveal the world, they also help create that view of the world into being.…”
Section: Theoretical Concepts: Bridging Cartography and Stsmentioning
confidence: 99%
“…Although participants' cartographic traces were a product of this experiment, the mapping process itself was just as important, situating our project within a post-representational cartographic framework (Kitchin 2010;Rossetto 2015;Caquard 2014). Our "map-score" experiments focus not on maps as end products, but on the immediate experience of places, emphasizing the importance of the body in exploring, mapping, and gaining a sensorial understanding of a place.…”
Section: Introductionmentioning
confidence: 99%
“…Roth et al [33] emphasized the opportunities for research in cartography, as "the possibility of digital interactivity requires us to re-envision map readers as the map users, and to address perceptual, cognitive, cultural and practical considerations that influence users' experience with interactive maps". Caquard [34] suggested that research on empirical cognitive maps could help to enhance the mental relationship between users and maps, as well as with places through maps. Hirtle and Raubal [35] point out that users perceive their environment differently, and that these differences should be reflected on their maps.…”
Section: Introductionmentioning
confidence: 99%